The Evolutionary Stability of Optimism, Pessimism and Complete Ignorance - Burkhard C. Schipper (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
We provide an evolutionary foundation to evidence that in some situations humans maintain optimistic or pessimistic attitudes towards uncertainty and are ignorant to relevant aspects of the environment. Players in strategic games face Knightian uncertainty about opponents' actions and maximize individually their Choquet expected utility. Our Choquet expected utility model allows for both an optimistic or pessimistic attitude towards uncertainty as well as ignorance to strategic dependencies. An optimist (resp. pessimist) overweights good (resp. bad) outcomes. A complete ignorant never reacts to opponents' change of actions. With qualifications we show that optimistic (resp. pessimistic) complete ignorance is evolutionary stable / yields a strategic advantage in submodular (resp. supermodular) games with aggregate externalities. Moreover, this evolutionary stable preference leads to Walrasian behavior in those classes of games.
Keywords: L13; D43; C72; D81; D01; C73; 330; ambiguity; Knightian uncertainty; Choquet expected utility; neo-additive capacity; Hurwicz criterion; Maximin; Minimax; Ellsberg paradox